Union structure and product quality differentiation - Nicola Meccheri; Cecilia Vergari (Global Labor Organization (GLO), 2024)
This paper investigates the issue of how alternative unionization structures in labour markets affect the choice of product quality differentiation by firms in product markets, and how this determines relative welfare outcomes of different union structures. In the presence of decentralized wage bargaining (firm-specific or coordinated unionization), increasing product differentiation not only reduces competition between firms but it also affects wage setting. Instead, when wage setting is centralized, wages do not depend on product quality differentiation in the product market but when the bargained wage is sufficiently high, the high-quality firm monopolizes the market. In turn, union wage setting does affect the endogenous choices by firms of the quality level of their products: especially when unionization is decentralized and unions have high relative bargaining power, the average product quality in the product market increases remarkably. However, as unionization reduces output, consumer surplus and overall welfare are always lower with respect to the case in which labour market is perfectly competitive, and decentralized unionization is generally welfare enhancing with respect to centralized unionization.
Keywords: J51; L13; L15; 330; unionization structures; vertical differentiation; welfare